Now Has Always Been the Time - Lyle, Ellyn; Latremouille, Jodi Marie; Jardine, David (Journal of the Canadian Association for Curriculum Studies, 2021)
Beginning from the assumption that we must learn to wonder as we wander, our writing here aims to advance theory and practice as they relate to walking. We understand walking as both an intentional physical activity and a curricular understanding of traversing with and through landscapes of topical relations in attunement with the Earth. We assume that insights gained through such attunement are accessed through deep consciousness of and presence with and, as such, we take up attunement in a variety of ways: spiritual (belonging in nature); intellectual (learning about relationships); physical (affecting the body); emotional (exploring love of nature); and imaginative (learning through creative engagement). Through critical, qualitative, creative, and arts-integrated approaches, we engage the praxis of living and being in relation.